Criminal Sanctions for Perpetrators of Motorclye Vehicle Theft Crimes - Moh Agung S. Moo (Estudiante Law Journal, 2026)
This study aims to determine criminal sanctions for perpetrators of motor vehicle theft crimes. The method used in this study is normative empirical research and uses a statutory and case approach as well as descriptive analysis techniques. The results of this study indicate that the consequences of perpetrators of the crime of motor vehicle theft accompanied by threats of violence can be subject to sanctions based on Articles 368 and 363 paragraph (1) in conjunction with Article 55 paragraph (1). Application of criminal sanctions in the Decision of the Limboto District Court Number 107/Pid.B/2020/PN Lbo which stated that Defendant I together with Defendant II, Defendant III, Defendant IV, and Defendant V were legally and convincingly proven guilty of committing the crime of extortion by force or threat of violence. In his decision, the judge stated that the defendants were sentenced to 8 (eight) months in prison each minus the periods of arrest and detention that had been served.